Biomechanics of distance running and running economy - Shim, J.
Background of this study 1. Main Themes of biomechanics Safety - Effectiveness - Efficiency Efficiency is related to the amount of efforts required to do certain mechanical task. The more efficient, the less efforts you need to put into the task. In other words, efficiency is economy of energy expenditure 2. Study method for running economy in most researches performance measures - the most appropriate criteria for investigations into relationships between performance and running mechanics experimental studies - experimental studies involving distance running performance are very difficult to control because so many factors affect performance Alternative criterion - researchers commonly use submaximal metabolic energy expenditure (VO2submax) as an alternative criterion